The Use of Digital Multimodal Approach in Teaching English Speaking Skill - Umroh; Juhana; Ruminda (PROJECT (Professional Journal of English Education), 2025)
This study investigates the development of students' English-speaking skills and self-confidence by implementing a digital multimodal presentation project in an English-speaking class. Employing a qualitative case study design, data were collected from 31 students and one English teacher through classroom observations, reflective journals, interviews, and document reviews. The findings indicate that the multimodal approach helped students improve their speaking proficiency by integrating various digital tools, fostering creativity, and reducing anxiety. However, some students faced challenges in terms of technical difficulties and limited English vocabulary. Despite these obstacles, the digital multimodal project significantly contributed to building students' self-confidence in speaking English. This method is recommended for further use to enhance students' engagement and communication skills in the language-learning process.